Clinical Use of Pulse Wave Analysis: Proceedings From a Symposium Sponsored by North American Artery. Issue 7 (23rd May 2015) - Townsend, Raymond R.; Black, Henry R.; Chirinos, Julio A.; Feig, Peter U.; Ferdinand, Keith C.; Germain, Michael; Rosendorff, Clive; Steigerwalt, Susan P.; Stepanek, Jan A.
<x xml:space="preserve">Abstract</x> The use of pulse wave analysis may guide the provider in making choices about blood pressure treatment in prehypertensive or hypertensive patients. However, there is little clinical guidance on how to interpret and use pulse wave analysis data in the management of these patients. A panel of clinical researchers and clinicians who study and clinically use pulse wave analysis was assembled to discuss strategies for using pulse wave analysis in the clinical encounter. This manuscript presents an approach to the clinical application of pulse waveform analysis, how to interpret central pressure waveforms, and how to use existing knowledge about the pharmacodynamic effect of antihypertensive drug classes in combination with brachial and central pressure profiles in clinical practice. The discussion was supplemented by case‐based examples provided by panel members, which the authors hope will provoke discussion on how to understand and incorporate pulse wave analysis into clinical practice.